“Gestión de los residuos sólidos de la actividad comercial en la asociación de comerciantes minoristas 15 de julio del cantón La Maná, año 2022” - Muñoz Vélez, Edgar Alejandro (2022)
Currently, the comprehensive management of ordinary solid waste is a challenge for all the nations of the world, with environmental implications for the soil, water and atmosphere. The present investigation was developed in the La Maná canton, Cotopaxi Province; It was addressed to the retailers of the Association July 15 in order to evaluate the management of solid waste from the commercial activity mentioned above. The research was descriptive. Analytical-synthetic, inductive-deductive and observation methods were used. In order to collect the pertinent information on the level of knowledge of the merchants on waste management, a census was carried out through the application of a survey that was made up of closed questions that allowed obtaining the opinions and criteria of the 92 involved. Multivariate analysis was applied through Cluster Analysis using Ward's hierarchical clustering method and a Euclidean distance of 10% in order to identify relatively homogeneous groups of cases. On the other hand, the Per Capita production of waste in the Association under study was determined. Statistical analysis allowed merchants to be classified into four groups: group 1 and 2 showed great interest in learning about and applying proper waste disposal; while group 2 and 3 reflected minimal interest in waste management. The per capita production of waste in the Association of Retail Merchants July 15